Targeting PD-L1 for PCNS-DLBCL: from molecular effects to clinical translation - Cao, Jiajia; Xiong, Shuzhen; Zhang, Shuni; Yue, Ningning; Wu, Chongyang (Frontiers in Immunology, 2025)
Primary central nervous system lymphoma (PCNSL) is a highly aggressive central nervous system lymphoma that has a high relapse rate and a 5-year survival rate of 30%-40% with conventional treatment. In about 95% of cases, Primary Central Nervous System Diffuse Large B-cell Lymphoma (PCNS-DLBCL) occurs. In some patients, the tumor microenvironment exhibited high levels of PD-L1, which may be linked to prognosis. The key mechanism for PD-L1 overexpression in EBV- tumor cells is the amplification of the 9p24.1 copy number, with signaling pathways such as JAK2 and NF-κB possibly playing a role in this process. Immune checkpoint inhibitors (anti-PD-1/PD-L1 mAb), particularly combined with BTK inhibitors, show promise in relapsed/refractory PCNSL. Still, there is no universally accepted therapeutic consensus. The blood-brain barrier limits drug penetration, and the spatiotemporal heterogeneity of PD-L1 remains a challenge. This paper discusses the expression of PD-L1 in PCNS-DLBCL and its relationship to prognosis, the efficacy of anti-PD-1 mAb and other drugs, and possible predictive markers of efficacy to provide a basis for anti-PD-1/PD-L1 mAb therapy, and the future of targeted PD-L1 therapy to achieve a high remission rate and individualized immunotherapy for PCNSL patients.